Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3109/10398562.2011.579971
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Substance Use by Patients with Psychosis Presenting to an Emergency Department: Changing Patterns

Abstract: Patients with co-existing mental health problems and substance use present a major problem for our emergency departments. Cannabis was the most common substance used. Youth, male gender and psychostimulant use are associated with violent presentations. A comprehensive history of alcohol and substance use is important to implement appropriate dual diagnosis treatment. Urine drug screening is recommended for patients who do not admit to substance use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 12 publications
4
21
1
7
Order By: Relevance
“…Table 4, which records specific drugs and their patterns of use in the sample, cannabis once again featured as the most commonly used drug among adolescents with dual diagnosis. This is similar to results from a study by Latt et al, 33 which also found cannabis to be the commonest illicit drug abused by patients with psychosis (schizophrenia and other psychotic disorders) presenting acutely to the emergency department. An important finding is the statistically significant relationship between cannabis as a debut drug and ongoing cannabis use.…”
Section: Substance Historysupporting
confidence: 90%
“…Table 4, which records specific drugs and their patterns of use in the sample, cannabis once again featured as the most commonly used drug among adolescents with dual diagnosis. This is similar to results from a study by Latt et al, 33 which also found cannabis to be the commonest illicit drug abused by patients with psychosis (schizophrenia and other psychotic disorders) presenting acutely to the emergency department. An important finding is the statistically significant relationship between cannabis as a debut drug and ongoing cannabis use.…”
Section: Substance Historysupporting
confidence: 90%
“…Psychiatric diagnoses were grouped into broad categories (affective disorders, schizophrenia and other psychosis, personality disorders, anxiety disorders, and others), and we did not discriminate between bipolar and unipolar affective disorders. We did not include data about laboratory tests objectively detecting drugs; nonetheless, it has been suggested that a urine drug screening can only identify a small additional rate (5%) of substance users [52]. Although it would have been interesting to assess details about reason for "acute" inpatient psychiatric admission, in this study, we focused specifically on a "snapshot" of comorbidity in a psychiatric ward over a 10-year period.…”
Section: Limitationsmentioning
confidence: 99%
“…Based on the literature and their clinical experience, they hypothesized an increase of the proportion of DD among all first psychiatric hospitalizations during the study period due to the increasing prevalence of substance-related disorders in the general population, an increased vulnerability to DD on behalf of specific population groups (e.g., new immigrants) [68][69][70], and, lastly, higher DD rates in involuntarily hospitalized patients because they may be more likely to show episodes of suicidal and violent behavior [52] compared to voluntarily admitted patients. Over the study period, DD with drugs decreased from 1996 to 2010, whereas DD with alcohol and DD with both drugs and alcohol increased.…”
Section: Epidemiology and Clinical Features Of Dd Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The substances used most frequently by persons with SMI are alcohol, followed by cannabis and stimulants; sedatives and hallucinogens are used less frequently [5,11,12]. Amphetamine use is greater in persons with psychotic disorders compared with the general population [13,14]. Studies have shown that both cannabis [15,16] and, to a greater extent, amphetamines [17,18] can provoke psychosis.…”
Section: Introductionmentioning
confidence: 99%